Combining Topological and Steric Constraints for the Preparation of Heteroleptic Copper(I) Complexes. Issue 38 (1st August 2014) - Mohankumar, Meera; Monti, Filippo; Holler, Michel; Niess, Frédéric; Delavaux‐Nicot, Béatrice; Armaroli, Nicola; Sauvage, Jean‐Pierre; Nierengarten, Jean‐François
Abstract Invited for the cover of this issue are Nicola Armaroli (ISOF, CNR, Bologna, Italy), Jean‐Pierre Sauvage (ISIS, University of Strasbourg), Jean‐François Nierengarten (University of Strasbourg and CNRS), and Béatrice Delavaux‐Nicot (LCC, CNRS, Toulouse). The image depicts an artistic view of a phosphorescent copper(I) complex with a glowing yin–yang symbol in the background because the formation of the compound is thermodynamically driven. Read the full text of the article at 10.1002/chem.201402429.